Understanding and optimization of hard magnetic compounds from first principles. Issue 1 (31st December 2021) - Miyake, Takashi; Harashima, Yosuke; Fukazawa, Taro; Akai, Hisazumi
ABSTRACT: First-principles calculation based on density functional theory is a powerful tool for understanding and designing magnetic materials. It enables us to quantitatively describe magnetic properties and structural stability, although further methodological developments for the treatment of strongly correlated 4f electrons and finite-temperature magnetism are needed. Here, we review recent developments of computational schemes for rare-earth magnet compounds, and summarize our theoretical studies on Nd2 Fe14 B and R Fe12 -type compounds. Effects of chemical substitution and interstitial dopants are clarified. We also discuss how data-driven approaches are used for studying multinary systems. Chemical composition can be optimized with fewer trials by the Bayesian optimization. We also present a data-assimilation method for predicting finite-temperature magnetization in wide composition space by integrating computational and experimental data. Graphical abstract: uf0001